Cutting Tools

A cutting tool with a cubic boron nitride sintered body and a MAlN layer addresses wear and chipping resistance issues by optimizing crystal orientation and residual stress, enhancing durability.

CN113874144BActive Publication Date: 2024-12-20SUMITOMO ELECTRIC HARDMETAL CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202080037997.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-08-06
Filing Date
2020-07-16
Publication Date
2024-12-20
Estimated Expiration
2040-07-16

AI Technical Summary

Technical Problem

Existing cutting tools with cubic boron nitride (cBN) sintered bodies have issues with wear resistance and chipping resistance, particularly when used for efficient cutting at high feed rates, as the crystal orientation of the constituent grains deviates, leading to inadequate hardness.

Method used

A cutting tool composed of a cubic boron nitride sintered body with a MAlN layer, where M represents titanium or chromium, having a specific atomic ratio, crystal orientation, and residual stress within certain ranges, enhances wear and chipping resistance.

Benefits of technology

The cutting tool exhibits improved wear resistance and chipping resistance due to the optimized MAlN layer structure, which includes a controlled crystal orientation and low compressive residual stress, resulting in enhanced durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113874144B_ABST
    Figure CN113874144B_ABST
Patent Text Reader

Abstract

A cutting tool, comprising a substrate composed of a cubic boron nitride sintered body, and a coating disposed on the substrate, wherein the coating comprises a MAlN layer, wherein M in the MAlN layer represents a metal element including titanium, chromium, or both, and the MAlN layer contains cubic crystal M x Al 1‑x N grains, the M x Al 1‑x The atomic ratio x of the metal element M in N is 0.3 or more and 0.7 or less, the content ratio of the cubic boron nitride is 20 volume % or more, and the MAlN layer is determined by electron backscatter diffraction image analysis on a cross section when the MAlN layer is cut along a plane including the normal line of the flank face. x Al 1‑x In the case of the crystal orientation of each grain of N, in the MAlN layer of the flank face, the normal direction of the (111) plane is within 25° with respect to the normal direction of the flank face. x Al 1‑x The proportion of the area occupied by N grains is greater than 45% and less than 75%, and the residual stress of the MAlN layer is greater than ‑2 GPa and less than ‑0.1 GPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a cutting tool. This patent application claims priority based on Japanese patent application No. 2019-144611 filed on August 6, 2019. All the contents described in the Japanese patent application are incorporated herein by reference. Background Art

[0002] Cubic boron nitride (hereinafter also referred to as "cBN") has a hardness second only to diamond, and has excellent thermal and chemical stability. In addition, cBN sintered bodies can be used as cutting tools for machining iron-based materials because they are more stable than diamond.

[0003] In order to improve the wear resistance of a cutting tool made of a cBN sintered body, a method of providing a coating on a substrate of the cBN sintered body has been studied.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 08-119774 Summary of the invention

[0007] The cutting tool of the present invention is

[0008] Including the front cutting edge and the back cutting edge,

[0009] The cutting tool is composed of a substrate composed of a cubic boron nitride sintered body and a coating provided on the substrate.

[0010] The cubic boron nitride sintered body contains cubic boron nitride.

[0011] The coating includes a MAlN layer,

[0012] The M in the MAlN layer represents a metal element including titanium, chromium, or both.

[0013] The MAlN layer contains cubic M x Al 1-x N grains,

[0014] The M x Al 1-x The atomic ratio x of the metal element M in N is 0.3 or more and 0.7 or less,

[0015] The content ratio of the cubic boron nitride relative to the cubic boron nitride sintered body is 20 volume % or more,

[0016] The MAlN layer is determined by electron backscatter diffraction image analysis using a field emission scanning microscope on a cross section of the MAlN layer cut along a plane including the normal line of the flank surface. x Al 1-x When the crystal orientation of each grain of N is plotted and a color map is drawn based on the crystal orientation, in the color map,

[0017] In the MAlN layer of the flank surface, the normal direction of the (111) plane is within 25° relative to the normal direction of the flank surface. x Al 1-x The area ratio of N grains is 45% or more and less than 75%,

[0018] The residual stress of the MAlN layer is greater than or equal to -2 GPa and less than or equal to 0.1 GPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] [ Figure 1 ] Figure 1 is a perspective view illustrating one approach of a cutting tool.

[0020] [ Figure 2 ] Figure 2 This is a schematic cross-sectional view of a cutting tool in one form of the present embodiment.

[0021] [ Figure 3 ] Figure 3 This is a schematic cross-sectional view of a cutting tool in another form of the present embodiment.

[0022] [ Figure 4 ] Figure 4 This is a schematic cross-sectional view of a cutting tool in another form of the present embodiment.

[0023] [ Figure 5 ] Figure 5 This is a schematic cross-sectional view of a cutting tool in another form of the present embodiment.

[0024] [ Figure 6 ] Figure 6 This is a schematic diagram of an enlarged SEM image of a cross section of the cutting tool according to the present embodiment.

[0025] [ Figure 7 ] Figure 7 This is an enlarged SEM image of a cross section of a cutting tool of a comparative example.

[0026] [ Figure 8 ] Figure 8 This is a diagram showing the distribution of the orientation of crystal grains in the TiAlN layer (MAlN layer) of the cutting tool according to the present embodiment.

[0027] [ Fig. 9 ] Fig. 9 This is a diagram showing the distribution of the orientation of crystal grains in the TiAlN layer (MAlN layer) of the cutting tool of the comparative example. DETAILED DESCRIPTION

[0028] [Problems to be Solved by the Invention]

[0029] For example, Japanese Patent Gazette No. 08-119774 (Patent Document 1) discloses a composite high-hardness material for tools, characterized in that: in a composite high-hardness material for tools having a substrate composed of a CBN sintered body containing more than 20 volume % cubic boron nitride, or a substrate composed of a diamond sintered body containing more than 40% diamond, there is at least one layer of hard heat-resistant coating at least at a position related to cutting, and the coating has at least one element selected from C, N and O, Ti, and Al as main components.

[0030] However, in the hard heat-resistant coating of the composite high-hardness material for tools described in Patent Document 1, there is a deviation in the crystal orientation of the constituent grains, and there is still room for improvement in hardness. Therefore, when applied to efficient cutting (cutting with a high feed rate, etc.), it is required to further improve the performance (such as wear resistance, chipping resistance, etc.).

[0031] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a cutting tool having excellent wear resistance and chipping resistance.

[0032] [Effects of the Invention]

[0033] According to the present invention, a cutting tool having excellent wear resistance and chipping resistance can be provided.

[0034] [Description of Embodiments of the Invention]

[0035] First, embodiments of the present invention will be listed and described.

[0036] [1] The cutting tool according to the present invention,

[0037] Including the front cutting edge and the back cutting edge,

[0038] The cutting tool is composed of a substrate composed of a cubic boron nitride sintered body and a coating provided on the substrate.

[0039] The cubic boron nitride sintered body contains cubic boron nitride.

[0040] The coating includes a MAlN layer,

[0041] The M in the MAlN layer represents a metal element including titanium, chromium, or both.

[0042] The MAlN layer contains cubic M x Al 1-x N grains,

[0043] The M x Al 1-x The atomic ratio x of the metal element M in N is 0.3 or more and 0.7 or less,

[0044] The content ratio of the cubic boron nitride relative to the cubic boron nitride sintered body is 20 volume % or more,

[0045] The MAlN layer is determined by electron backscatter diffraction image analysis using a field emission scanning microscope on a cross section of the MAlN layer cut along a plane including the normal line of the flank surface. x Al 1-x When the crystal orientation of each grain of N is determined and a color diagram is drawn based on the crystal orientation, in the color diagram,

[0046] In the MAlN layer of the flank surface, the normal direction of the (111) plane is within 25° relative to the normal direction of the flank surface. x Al 1-x The area ratio of N grains is 45% or more and less than 75%,

[0047] The residual stress of the MAlN layer is greater than or equal to -2 GPa and less than or equal to 0.1 GPa.

[0048] In the MAlN layer (e.g., TiAlN layer) on the back face of the cutting tool, the MAlN layer has a normal direction of the (111) plane within 25° relative to the normal direction of the back face in the color diagram. x Al 1-x The number of particles occupied by N grains exists in a predetermined ratio. Therefore, the hardness of the MAlN layer in the flank is excellent. In addition, since the compressive residual stress of the MAlN layer is low, chipping is suppressed. That is, the cutting tool can have excellent wear resistance and excellent chipping resistance by having the above-mentioned structure. Here, "chipping resistance" refers to the tolerance to the generation of small defects in the coating.

[0049] [2] The metal element M further preferably includes at least one element selected from the group consisting of boron, silicon, vanadium, zirconium, niobium, molybdenum, hafnium, tantalum and tungsten. By such a provision, the cutting tool has better wear resistance, excellent heat resistance and excellent lubricity.

[0050] [3] In the MAlN layer of the back face, the normal direction of the (111) plane is within 25° relative to the normal direction of the back face. x Al 1-x The area ratio of the N crystal grains is preferably 55% or more and less than 75%. By such a regulation, the cutting tool has better wear resistance and better chipping resistance.

[0051] [4] The thickness of the coating is preferably 0.5 μm or more and less than 10 μm. With this provision, the cutting tool has better wear resistance and better chipping resistance.

[0052] [5] Preferably, the MAlN layer further contains Ar, and the content of Ar relative to the MAlN layer is 0.1 at % to 5 at %. With this provision, the cutting tool has a more excellent chipping resistance.

[0053] [6] In a cross section when the MAlN layer is cut along a plane including the normal line of the flank surface, the number of droplets n per 50 μm length of the MAlN layer on the flank surface is D It is preferably not more than 2. By defining it in this way, the cutting tool has further excellent wear resistance and further excellent chipping resistance.

[0054] [Detailed description of embodiments of the present invention]

[0055] An embodiment of the present invention (hereinafter referred to as "this embodiment") is described below. However, this embodiment is not limited to this. In this specification, the expression in the form of "A to Z" refers to the upper and lower limits of the range (i.e., above A and below Z). When no unit is recorded in A and only the unit is recorded in Z, the unit of A is the same as the unit of Z. In addition, in this specification, for example, such as "TiN", when a compound is represented by a chemical formula that does not limit the composition ratio of the constituent elements, the chemical formula includes all the composition ratios (element ratios) that have been known to the public. In this case, the above chemical formula includes not only stoichiometric compositions, but also non-stoichiometric compositions. For example, the chemical formula of "TiN" includes not only the stoichiometric composition "Ti1N1", but also includes, for example, "Ti1N 0.8 " Such a non-stoichiometric composition. This also applies to the description of compounds other than "TiN".

[0056] 《Surface-coated cutting tools》

[0057] The cutting tool of the present invention is

[0058] Including the front cutting edge and the back cutting edge,

[0059] The cutting tool is composed of a substrate composed of a cubic boron nitride sintered body and a coating provided on the substrate.

[0060] The cubic boron nitride sintered body contains cubic boron nitride.

[0061] The coating includes a MAlN layer,

[0062] The M in the MAlN layer represents a metal element including titanium, chromium, or both.

[0063] The MAlN layer contains cubic M x Al 1-x N grains,

[0064] The M x Al 1-x The atomic ratio x of the metal element M in N is 0.3 or more and 0.7 or less,

[0065] The content ratio of the cubic boron nitride relative to the cubic boron nitride sintered body is 20 volume % or more,

[0066] The MAlN layer is determined by electron backscatter diffraction image analysis using a field emission scanning microscope on a cross section of the MAlN layer cut along a plane including the normal line of the flank surface. x Al 1-x When the crystal orientation of each grain of N is determined and a color diagram is drawn based on the crystal orientation, in the color diagram,

[0067] In the MAlN layer of the flank surface, the normal direction of the (111) plane is within 25° relative to the normal direction of the flank surface. x Al 1-x The area ratio of N grains is 45% or more and less than 75%,

[0068] The residual stress of the MAlN layer is greater than or equal to -2 GPa and less than or equal to 0.1 GPa.

[0069] The surface-coated cutting tool involved in this embodiment (hereinafter sometimes referred to as "cutting tool") can be, for example, a drill, an end mill, an indexable cutting insert for a drill, an indexable cutting insert for an end mill, an indexable cutting insert for milling, an indexable cutting insert for turning, a metal saw, a gear cutting tool, a reamer, a tap, etc.

[0070] Figure 1 1 is a perspective view illustrating one embodiment of a cutting tool. The cutting tool 10 having such a shape can be used as an indexable cutting insert for turning.

[0071] Figure 1The cutting tool 10 shown has a surface including an upper surface, a lower surface and four side surfaces, and is generally in the shape of a quadrangular prism that is slightly thinner in the upper and lower directions. In addition, a through hole is formed in the cutting tool 10 that penetrates the upper and lower surfaces, and in the boundary portions of the four side surfaces, adjacent side surfaces are connected to each other through arc surfaces.

[0072] In the above-mentioned cutting tool 10, usually, the upper surface and the lower surface form the front cutting face 1a, the four side surfaces (and the arc surface connecting these side surfaces to each other) form the back cutting face 1b, and the surface connecting the front cutting face 1a and the back cutting face 1b forms the cutting edge surface 1c. The "front cutting face" refers to the surface that discharges the chips cut from the cut material. The "back cutting face" refers to the surface of which a part contacts the cut material. The cutting edge surface is included in the part that constitutes the cutting edge of the cutting tool.

[0073] In the case where the cutting tool is an indexable cutting insert, the cutting tool 10 may include a shape having a chip breaker or a shape not having a chip breaker. Figure 1 In the figure, the shape of the cutting edge of the cutting tool is represented by a plane (cutting edge surface 1c), but the shape of the cutting edge is not limited to this. That is, the shape of the cutting edge includes a sharp edge (the edge where the front cutting edge and the back cutting edge intersect) (for example, Figure 3 ) and negative land (the shape of the chamfer) (e.g. Figure 2 ) shape.

[0074] Above, use Figure 1 to Figure 3 The shape of the cutting tool 10 and the names of the various parts are described, but in the base material of the cutting tool involved in this embodiment, the same terms as above are used corresponding to the shape and the names of the various parts of the cutting tool 10. That is, the base material of the cutting tool has a rake face and a flank face. In addition, the base material may also have a cutting edge face connecting the rake face and the flank face.

[0075] The cutting tool 10 includes a substrate 11 and a MAlN layer 12 ( Figure 4 In addition to the MAlN layer 12, the cutting tool 10 may further include a base layer 13 ( Figure 5 The cutting tool 10 may further include a surface layer 14 ( Figure 5 ). Other layers such as the base layer 13 and the surface layer 14 will be described later.

[0076] It should be noted that the above-mentioned layers provided on the above-mentioned substrate are sometimes collectively referred to as "films". That is, the above-mentioned cutting tool 10 includes a film 20 ( Figure 2 , Figure 3The coating 20 includes the MAlN layer 12 ( Figure 4 In addition, the coating 20 may further include the base layer 13 or the surface layer 14 ( Figure 5 ).

[0077] <Base Material>

[0078] (Cubic boron nitride sintered body)

[0079] The substrate of the present embodiment is composed of a cubic boron nitride sintered body (cBN sintered body). The cubic boron nitride sintered body contains cubic boron nitride. In one aspect of the present embodiment, the cubic boron nitride sintered body preferably further contains a binder.

[0080] (Cubic Boron Nitride)

[0081] In the present embodiment, "cubic boron nitride" refers to cubic boron nitride crystal grains. That is, the cubic boron nitride sintered body contains cubic boron nitride.

[0082] The average particle size R of the cubic boron nitride is preferably 0.8 μm or more and 5 μm or less, and more preferably 1 μm or more and 4 μm or less.

[0083] The average particle size R can be obtained by a cutting method using a scanning electron microscope (SEM). Specifically, first, any surface or cross section of the cubic boron nitride sintered body is mirror-finished. Then, the processed surface of the cubic boron nitride sintered body is observed by SEM at a magnification of 1000 to 10000 times to obtain a SEM image.

[0084] Then, a circle is drawn on the SEM image, and 8 straight lines are drawn radially from the center of the circle (the intersection angles between the straight lines are almost equal) to the periphery of the circle. In this case, it is preferred to set the above observation magnification and the diameter of the circle so that the number of cubic boron nitride (grains) carried on each straight line is about 10 to 50.

[0085] Next, the number of grain boundaries of cubic boron nitride that cross in each straight line is counted, and the average slice length is obtained by dividing the length of the straight line by the number of the crosses. Finally, the average slice length obtained is multiplied by 1.128 and the numerical value obtained is used as the average particle size of cubic boron nitride (this method is a method for calculating the nominal particle size based on ASTM standards). It should be noted that such an average particle size is more preferably obtained by the following method: using multiple SEM images, the average particle size is obtained for each image by the above method, and the average value of the average particle size is used as the average particle size. In addition, in the determination by the above method, the particle size of particles (for example, grains of wurtzite-type boron nitride) other than cubic boron nitride may be contained, but even in the case of the particle size containing other particles in this way, it is also regarded as the average particle size of cubic boron nitride.

[0086] The content ratio of the above-mentioned cubic boron nitride relative to the above-mentioned cubic boron nitride sintered body is 20 volume % or more, preferably 20 volume % or more and 97 volume % or less, and more preferably 20 volume % or more and 80 volume % or less. The content ratio of the above-mentioned cubic boron nitride can be obtained by photographing the cross-section sample of the above-mentioned cubic boron nitride sintered body using SEM, and performing image analysis on the photographic image. That is, the crystal grains of the cubic boron nitride in the predetermined field of view can be determined, and the sum of the areas of the determined crystal grains can be calculated by image processing, and divided by the area of ​​the field of view to calculate. In addition, it is preferred that in the same cubic boron nitride sintered body, the above-mentioned image analysis is performed in multiple fields of view (for example, more than 5 fields of view), and the average value is used as the content ratio of cubic boron nitride. In the above-mentioned image processing, image analysis type particle size distribution software ("Mac-View" manufactured by "Mac-View Co., Ltd.") can be appropriately used. It should be noted that the above-mentioned “predetermined field of view” may be the same as the field of view when the average grain size of the above-mentioned cubic boron nitride grains is calculated.

[0087] The ratio obtained by the above method is the area ratio of cubic boron nitride in the field of view, but in this embodiment, the ratio is treated as a volume ratio. That is, when the area ratio of cubic boron nitride obtained by the above method is 20%, it is considered that the content ratio of cubic boron nitride relative to the cubic boron nitride sintered body is 20 volume%.

[0088] (Adhesive)

[0089] In this embodiment, the "binder" refers to a substance that binds the crystal grains of the cubic boron nitride to each other. The binder preferably contains a compound consisting of at least one element selected from the group consisting of Group 4 elements, Group 5 elements, Group 6 elements, Al (aluminum) and Si (silicon) in the periodic table and at least one element selected from the group consisting of C (carbon), N (nitrogen), B (boron) and O (oxygen).

[0090] As the above-mentioned Group 4 elements, for example, Ti (titanium), Zr (zirconium), and Hf (hafnium) can be listed. As the Group 5 elements, for example, V (vanadium), Nb (niobium), and Ta (tantalum) can be listed. As the above-mentioned Group 6 elements, for example, Cr (chromium), Mo (molybdenum), and W (tungsten) can be listed. The components contained in the above-mentioned adhesive can be obtained by analyzing the sample containing the cut surface of the above-mentioned cutting tool in the area corresponding to the adhesive using energy dispersive X-ray spectroscopy (SEM-EDX) attached to the SEM. The observation magnification at this time is, for example, 10,000 times.

[0091] Examples of compounds consisting of at least one element selected from the group consisting of Group 4 elements, Group 5 elements, Group 6 elements, Al and Si in the periodic table and at least one element selected from the group consisting of C, N, B and O include: nitrides such as TiN and AlN; carbides such as TiC and WC; borides such as TiB2 and AlB2; oxides such as Al2O3; or TiCN, AlON, SiAlON, SiTiAlON, etc.

[0092] (Unavoidable impurities)

[0093] Without prejudice to the effect exerted by the present invention, the above-mentioned cubic boron nitride sintered body may also contain inevitable impurities. Inevitable impurities refer to the general term for elements and compounds that may be contained in trace amounts in the raw materials of the cubic boron nitride sintered body or in the manufacturing process. The content (volume %) of each element and compound included as inevitable impurities is respectively 0 volume % or more and 5 volume % or less, and their sum (i.e., the total content of trace impurities) is 0 volume % or more and 5 volume % or less. Therefore, the inevitable impurities may be contained in the above-mentioned cubic boron nitride sintered body or may not be contained. As inevitable impurities, for example, Li, Mg, Ca, Sr, Ba, Be, Si, Ga, La, Fe, Cu, etc. can be listed.

[0094] <Lamination>

[0095] The coating involved in this embodiment includes an MAlN layer. M in the MAlN layer represents a metal element including titanium, chromium or both. The "coating" has the function of improving the chipping resistance, wear resistance and many other properties of the cutting tool by covering at least a portion of the substrate (for example, a portion of the front cutting edge and a portion of the back cutting edge). The coating preferably covers the entire surface of the substrate. However, even if a portion of the substrate is not covered by the coating, or the composition of the coating is partially different, it does not deviate from the scope of this embodiment.

[0096] The thickness of the above-mentioned film is preferably greater than 0.5μm and less than 10μm, more preferably greater than 1μm and less than 5μm. Here, the thickness of the film refers to the sum of the thicknesses of the layers constituting the film. As "layers constituting the film", for example, the above-mentioned MAlN layer, the intermediate layer described later, the above-mentioned base layer and other layers such as the surface layer can be listed. The thickness of the above-mentioned film can be calculated, for example, by the following method: use SEM to measure any 10 points in the cross-section sample parallel to the normal direction of the surface of the substrate, and calculate the average value of the thickness of the measured 10 points. The measurement multiple at this time is, for example, 10000 times. The same is true for measuring the thickness of the above-mentioned MAlN layer, the above-mentioned intermediate layer, the above-mentioned base layer and the surface layer. As an SEM, for example, JEM-2100F (trade name) manufactured by "Japan Electronics Co., Ltd." can be listed.

[0097] (MAlN layer)

[0098] The MAlN layer contains cubic M x Al 1-x That is, the MAlN layer contains polycrystalline M x Al 1-x N layer. Cubic M x Al 1-x N crystal grains can be identified, for example, by the pattern of diffraction peaks obtained by X-ray diffraction.

[0099] The M in the MAlN layer represents a metal element. The metal element M includes titanium, chromium, or both. In one aspect of the present embodiment, the metal element M preferably further contains at least one element selected from the group consisting of boron, silicon, vanadium, zirconium, niobium, molybdenum, hafnium, tantalum and tungsten (hereinafter sometimes referred to as the "third element"). It should be noted that boron is generally considered to be a semi-metal with intermediate properties between metal elements and non-metal elements, but in the MAlN layer of the present embodiment, elements with free electrons are considered to be metals, so boron is also included in the range of metal elements.

[0100] In one aspect of the present embodiment, the metal element M is preferably titanium. That is, the coating preferably includes a TiAlN layer as the MAlN layer, and the TiAlN layer preferably contains cubic Ti. x Al 1-x Here, the TiAlN layer contains polycrystalline Ti x Al 1-x N layer. Cubic Ti x Al 1-x N crystal grains can be identified, for example, by the pattern of diffraction peaks obtained by X-ray diffraction.

[0101] The above Mx Al 1-x The atomic ratio x of the metal element M in N is 0.3 to 0.7, preferably 0.32 to 0.55. The above x can be obtained by performing elemental analysis on the entire MAlN layer of the above cross-section sample using energy dispersive X-ray spectroscopy (SEM-EDX) attached to the SEM. The observation magnification at this time is, for example, 20,000 times. Specifically, the value of the above x is obtained by measuring any 10 points in the MAlN layer of the above cross-section sample, and the average value of the values ​​of the 10 points obtained is taken as x in the above MAlN layer. Here, in the case where the above metal element M includes multiple metal elements, the sum of the atomic ratios of each metal element is set to the atomic ratio x of the above metal element M. In addition, the "arbitrary 10 points" are selected from different grains in the above MAlN layer. The same is true for the determination of the content ratio of Ar in the MAlN layer described later. As the above EDX device, for example, JED-2300 (trade name) manufactured by "JEOL Ltd." can be cited.

[0102] When the metal element M contains titanium, x Al 1-x The atomic ratio w of titanium in N is preferably greater than 0 and not more than 0.7, more preferably not less than 0.2 and not more than 0.6. When the metal atom M is only titanium, the atomic ratio x of the metal element M naturally matches the atomic ratio w of titanium.

[0103] When the metal element M contains chromium, x Al 1-x The atomic ratio y of chromium in N is preferably greater than 0 and less than 0.7, more preferably greater than 0.2 and less than 0.6. When the metal atom M is only chromium, the atomic ratio x of the metal element M naturally matches the atomic ratio y of chromium.

[0104] When the metal element M contains a third element, x Al 1-x The atomic ratio z of the third element in N is preferably greater than 0 and not more than 0.7, more preferably not less than 0.01 and not more than 0.3. Here, when a plurality of metal elements are contained as the third element, the atomic ratio z of the third element is the sum of the atomic ratios of the metal elements.

[0105] The thickness of the MAlN layer is preferably 0.05 μm to 10 μm, more preferably 0.3 μm to 4 μm. In the case where the coating includes multiple MAlN layers, the thickness of the MAlN layer refers to the thickness of each layer. The thickness can be measured, for example, by observing the cross section of the cutting tool using an SEM at a magnification of 10,000 times.

[0106] The coating may include one MAlN layer or multiple layers (e.g., 2 to 10 layers). The MAlN layer may be alternately stacked with other layers such as an intermediate layer described later. In one aspect of the present embodiment, the MAlN layer itself may also form a multilayer structure.

[0107] (Crystal orientation in the MAlN layer on the flank surface)

[0108] In this embodiment, the MAlN layer is determined by electron backscatter diffraction image analysis using a field emission scanning microscope on a cross section of the MAlN layer cut along a plane including the normal line of the flank surface. x Al 1-x When the crystal orientation of each grain of N is determined and a color diagram is drawn based on the crystal orientation, in the color diagram,

[0109] In the MAlN layer of the flank surface, the normal direction of the (111) plane is within 25° relative to the normal direction of the flank surface. x Al 1-x The area ratio of N grains (hereinafter sometimes referred to as "(111) plane-oriented grains") is 45% or more and less than 75%, more preferably 55% or more and less than 75%.

[0110] Here, refer to Figure 6 The specific method of drawing the above color map is described. First, a MAlN layer is formed on a substrate based on the manufacturing method described later. Then, the formed MAlN layer is cut to obtain a cross section perpendicular to the MAlN layer including the substrate, etc. That is, the MAlN layer is cut in a manner such that a cut surface is exposed after the MAlN layer is cut with a plane including the normal line of the above-mentioned back blade. Then, the cut surface is polished using water-resistant polishing paper (containing SiC sand abrasive as an abrasive).

[0111] It should be noted that in the above-mentioned cutting, the surface of the MAlN layer 12 (the surface of the coating when other layers are formed on the MAlN layer 12) is tightly fixed on a sufficiently large holding plate using wax or the like, and then a cutting machine with a rotating blade is used to cut in a direction perpendicular to the plate (cut in a manner that the rotating blade and the plate are as perpendicular as possible). The cutting can be performed at any part of the MAlN layer 12 as long as it is performed relative to such a vertical direction, but it is preferably cut near the part related to cutting.

[0112] The polishing was performed using the water-resistant polishing paper (#400, #800, and #1500, respectively). The number (#) of the water-resistant polishing paper means the difference in the particle size of the abrasive, and the larger the number, the smaller the particle size of the abrasive.

[0113] Next, the polished surface is further smoothed by ion milling using Ar ions. The conditions of the ion milling are as follows.

[0114] Accelerating voltage: 6kV

[0115] Irradiation angle: 0° from the normal direction of the MAlN layer (i.e., the straight line direction parallel to the thickness direction of the MAlN layer in the cut surface)

[0116] Irradiation time: 8 hours.

[0117] Next, the smoothed section (mirror surface) is observed using a field emission scanning electron microscope (FE-SEM) (product name: "SU6600", manufactured by Hitachi High Tech Novel Devices) equipped with an electron backscatter diffraction device (EBSD device), and the obtained observation image is subjected to EBSD analysis. The observation position of the smoothed section is not particularly limited, but it is preferred to observe the vicinity of the cutting edge portion. It should be noted that the observation magnification of the FE-SEM is set to 5000 times.

[0118] In addition, for EBSD analysis, data is collected sequentially by positioning the focused electron beam on each pixel. The normal of the sample surface (cross section of the MAlN layer after smoothing) is tilted 70° relative to the incident beam, and the analysis is performed at 15kV. A high current mode matching an opening diameter of 60μm or 120μm is used. Data collection is performed on the cross section at a step size of 0.1μm / step for 60×500 sites in a surface area (observation area) equivalent to 6μm (thickness direction of the MAlN layer) × 50μm (direction parallel to the interface of the MAlN layer). The number of measurement fields at this time is set to 3 or more.

[0119] The results of the above EBSD analysis are analyzed using commercially available software (trade name: "Orientation Imaging Microscopy Ver6.2", manufactured by EDAX) to draw the above color map. Specifically, first determine the crystal orientation of each grain contained in the cross section of the MAlN layer 12. Then, based on the crystal orientation of each obtained grain, determine the crystal orientation of each grain in the normal direction of the surface of the MAlN layer 12. Then, draw a color map based on the determined crystal orientation. In order to draw the color map, the "Cristal Direction MAP" method included in the above software can be used. It should be noted that the color map is drawn on the cut surface along the entire thickness direction of the observed MAlN layer 12. In addition, a portion of the grains that appear outside the measurement field of view are also counted as 1.

[0120] exist Figure 6 In FIG. 1 , each region surrounded by a solid line and shaded by an oblique line is a (111)-oriented grain 12a. In addition, each region surrounded by a solid line and not shaded is a grain that does not correspond to a (111)-oriented grain. Figure 6 In FIG. 1 , the grains 12a whose normal direction to the (111) plane is within 25° relative to the normal direction to the surface of the MAlN layer 12 are indicated by oblique hatching. Figure 6 There is an area indicated by black in the figure, which is regarded as a region of grains whose crystal orientation is not determined in the above method.

[0121] Next, in the color map of each field of view, the area of ​​the (111)-oriented grains in the MAlN layer of the flank surface and the area of ​​all grains in the MAlN layer of the flank surface are calculated, and the ratio of the area occupied by the (111)-oriented grains is calculated based on the following formula. Here, "the area of ​​all grains" refers to "the area of ​​the entire measurement field of view".

[0122] The ratio of the area occupied by (111)-plane oriented grains = {area of ​​(111)-plane oriented grains / area of ​​the entire measurement field of view} × 100 (%)

[0123] The ratio of the area occupied by the (111)-plane oriented grains obtained in each field of view is averaged to calculate the ratio of the area occupied by the (111)-plane oriented grains. Here, when the coating includes multiple MAlN layers, it is sufficient that at least one of the multiple MAlN layers satisfies the ratio of the area occupied by the (111)-plane oriented grains.

[0124] (Residual stress in MAlN layer)

[0125] The residual stress of the MAlN layer is -2 GPa to 0.1 GPa, preferably -1.5 GPa to 0.3 GPa. When the coating includes a plurality of MAlN layers, at least one of the plurality of MAlN layers satisfies the residual stress value.

[0126] The residual stress of the MAlN layer refers to the internal stress (intrinsic strain) present in the MAlN layer. Among the residual stresses of the MAlN layer, the residual stress represented by a negative value (negative number) (unit: "GPa" is used in this embodiment) is called compressive residual stress. It should be noted that among the residual stresses of the MAlN layer, the residual stress represented by a positive value (positive number) (unit: "GPa" is used in this embodiment) is called tensile residual stress.

[0127] The residual stress can be determined by using 2θ-sin 2 Specifically, by using the 2θ-sin 2 The ψ method (tilt method) analyzes the MAlN layer at any three points in the MAlN layer, and takes the average value of the residual stresses obtained at these three points as the residual stress in the MAlN layer. For the arbitrary three points, three points anywhere can be selected, or three points on the back face can also be selected.

[0128] The above uses the 2θ-sin 2 The measurement conditions in the ψ method (tilt method) are as follows: Here, the thickness of the sample used for measurement is 5 μm.

[0129] (Measurement conditions)

[0130]

[0131] (Ar content in MAlN layer)

[0132] The MAlN layer may further contain Ar. The content ratio (atomic percentage) of the Ar relative to the MAlN layer is preferably 0.1 at% to 5 at%, more preferably 0.1 at% to 1 at%. The content ratio of Ar in the MAlN layer can be determined by analyzing the entire MAlN layer of the cross-section sample using SEM-EDX. In the case where the coating includes multiple MAlN layers, it is sufficient that at least one of the multiple MAlN layers satisfies the content ratio of Ar.

[0133] (Number of droplets of MAlN layer on the flank surface)

[0134] In this embodiment, in a cross section when the MAlN layer is cut along a plane including a normal line of the flank surface, the number n of droplets per 50 μm length of the MAlN layer on the flank surface is D It is preferably 2 or less, and more preferably 0 or more and 2 or less.

[0135] In the present embodiment, the “droplets” refer to particles which are metal particles existing in a layer constituting the coating (for example, an MAlN layer such as a TiAlN layer) and have a predetermined size as described below.

[0136] The number of the above-mentioned droplets is counted by the following steps. First, use SEM to observe the cross-section of the above-mentioned cutting tool at a magnification of 5000 times to obtain a SEM image. At this time, the SEM image is acquired in a manner that the above-mentioned MAlN layer is continuously included in the length range of 50μm (the length in the direction perpendicular to the thickness direction of the MAlN layer). As long as the above-mentioned MAlN layer is included in the above-mentioned length range of 50μm, the number of SEM images acquired is not particularly limited, and it can be one field of view or multiple fields of view. In the case of acquiring SEM images in multiple fields of view, the SEM images can also be connected, and then the number of droplets can be counted. The size of one field of view can be, for example, 25μm×20μm.

[0137] The obtained SEM images were visually confirmed, and attention was paid to the components present in the MAlN layer (e.g., Figure 7 Next, find the length L of the long side of the rectangle circumscribing the approximately circular portion. a (μm) and the length of the short side L b (μm). Here, the rectangle is set so that the long side or the short side is parallel to the main surface of the substrate. In this embodiment, "parallel" is not limited to geometric parallelism, but also includes the concept of approximately parallelism. a and L b When the following conditions are satisfied, the approximately circular portion is counted as a droplet.

[0138] 1≤L a / L b <1.3、and 0.1<L a

[0139] The number of the droplets is counted in at least three "continuous length ranges of 50 μm", and the average value thereof is taken as the number of the droplets.

[0140] When the coating includes a plurality of MAlN layers, at least one of the plurality of MAlN layers only needs to satisfy the condition regarding the number of droplets.

[0141] (Other layers)

[0142] As long as the effect of the present embodiment is not impaired, the coating may further include other layers. As the other layers, for example, there can be listed: a base layer disposed between the substrate and the MAlN layer; a surface layer disposed on the MAlN layer; and an intermediate layer disposed between the base layer and the MAlN layer, or between the MAlN layer and the surface layer. As long as they can be distinguished from the MAlN layer, the compositions of the base layer, the surface layer and the intermediate layer may be the same or different. The base layer may be, for example, a layer composed of a compound represented by TiN. The surface layer may be, for example, a layer composed of a compound represented by TiCN. The intermediate layer may be, for example, a layer composed of a compound represented by AlCrN. The composition of the other layers may be obtained by analyzing the entire other layers of the cross-section sample using SEM-EDX. Within the range that does not impair the effect of the present embodiment, the thickness of the other layers is not particularly limited, and for example, it may be listed as 0.1 μm or more and 2 μm or less.

[0143] 《Method for manufacturing surface-coated cutting tools》

[0144] The manufacturing method of the cutting tool according to the present embodiment includes:

[0145] a step of preparing the substrate (hereinafter sometimes referred to as "first step"); and

[0146] A step of forming the MAlN layer on the substrate by high-power pulse sputtering (hereinafter, sometimes referred to as “second step”).

[0147] High Power Pulse Sputtering (HiPIMS) is a type of sputtering method. HiPIMS is a film forming method in which atoms of a target (raw material) are deposited on a substrate or the like by applying a pulse of electric power greater than that in a normal sputtering method and discharging the target (raw material) to form a discharge.

[0148] In the HiPIMS method, after a substrate is set in the device and a target is set as a cathode, a negative voltage is applied to the target to generate a discharge. At this time, an inert gas (e.g., Ar gas) is filled in the device under reduced pressure. The inert gas in the device is ionized by glow discharge, and the ions of the inert gas collide with the target surface at high speed. The target atoms are ejected by the collision, and are deposited on the substrate to form a film.

[0149] The HiPIMS method forms a film based on the above principle, so it is difficult to generate droplets compared to the arc cathode ion plating method. In addition, it can be considered that by using the HiPIMS method, a MAlN layer such as a TiAlN layer is formed on a substrate composed of a cubic boron nitride sintered body, and a large amount of ions of target material elements, inert gas ions, and reactive gas ions generated by the large power of the HiPIMS method are incident on the cBN particles in a pulsed manner in a short time. Therefore, the inventors believe that it is easy to generate the MAlN layer. x Al 1-x N (111) oriented grains.

[0150] <Step 1: Step of Preparing a Base Material>

[0151] In the first step, a substrate is prepared. As the substrate, a substrate composed of the cubic boron nitride sintered body is prepared. A commercially available substrate can also be used as the substrate. In addition, the substrate can also be manufactured by the method described in the embodiments described later. Then, the cubic boron nitride sintered body is subjected to predetermined cutting edge processing such as chamfering treatment, thereby manufacturing the substrate composed of the cubic boron nitride sintered body.

[0152] <Second step: step of forming MAlN layer>

[0153] In the second step, the MAlN layer is formed on the substrate by high-power pulse sputtering, which may be a method of using a target in which the amounts of metal elements M (eg, Ti) and Al are adjusted according to the composition of the MAlN layer to be formed.

[0154] For example, the second step can be performed as follows. First, a blade of any shape as a substrate is installed in the chamber of the film forming device. At this time, the substrate is arranged in a manner such that the back blade surface is opposite to the above-mentioned target. For example, the substrate is installed on a substrate holder on a centrally rotatable rotating table in the chamber of the film forming device. A bias power supply is connected to the substrate holder. While the above-mentioned rotating table is rotated in the center of the chamber, Ar gas and nitrogen gas are introduced. In addition, while the substrate is maintained at a temperature of 400 to 600°C, a reaction gas pressure of 300 mPa to 3000 mPa, and a bias power supply voltage of -200 to 20V, sputtering power (for example, an average power of 10 kW, a frequency of 2000 Hz, and a pulse width of 100 μs) is applied to the target for forming the MAlN layer. As a result, metal atoms fly out of the target for forming the MAlN layer, and the sputtering power is stopped after a predetermined time, thereby forming a MAlN layer on the surface of the substrate. At this time, by adjusting the film forming time, the thickness of the MAlN layer can be adjusted within a predetermined range. In addition to the portion involved in cutting (for example, the rake face and the flank face near the cutting edge), the second step may form the MAlN layer on the surface of the substrate other than the portion involved in cutting.

[0155] (Raw material for MAlN layer)

[0156] In the second step, the raw material of the MAlN layer contains metal elements M and Al. When the MAlN layer is a TiAlN layer, the raw material of the TiAlN layer contains Ti and Al. Examples of the raw material of the TiAlN layer include powder sintered alloys of Ti and Al.

[0157] In this embodiment, the reaction gas may be appropriately set according to the composition of the MAlN layer. Examples of the reaction gas include a mixed gas of nitrogen gas and an inert gas.

[0158] In one embodiment of the present invention, the surface of the substrate may be etched before the MAlN layer is formed. The etching conditions include the following conditions:

[0159] Inert gas: Ar gas

[0160] Temperature: 550℃

[0161] Pressure: 1000mPa

[0162] Voltage: Pulse DC voltage (800V, frequency 50kHz, pulse width 10μs)

[0163] Processing time: 20 to 30 minutes

[0164] <Other Processes>

[0165] In the manufacturing method involved in the present embodiment, in addition to the above-mentioned process, a process of forming a base layer on a substrate; a process of forming an intermediate layer on the above-mentioned base layer or the above-mentioned MAlN layer; a process of forming a surface layer on the above-mentioned MAlN layer; and a process of surface treatment, etc. can be appropriately performed. In the case of forming other layers such as the above-mentioned base layer, intermediate layer and surface layer, other layers can be formed by existing methods. Specifically, for example, a physical vapor deposition method (PVD method) different from the HiPIMS method can be cited to form the above-mentioned other layers. As a surface treatment process, for example, surface treatment using a medium loaded with diamond powder on an elastic material can be cited.

[0166] The above description includes the following additional features.

[0167] (Note 1)

[0168] A surface-coated cutting tool comprises a rake face and a flank face,

[0169] The surface-coated cutting tool comprises a substrate composed of a cubic boron nitride sintered body and a coating provided on the substrate.

[0170] The cubic boron nitride sintered body contains cubic boron nitride.

[0171] The coating includes a TiAlN layer,

[0172] The TiAlN layer contains cubic Ti x Al 1-x N grains,

[0173] The Ti x Al 1-x The atomic ratio x of Ti in N is 0.3 or more and 0.7 or less,

[0174] The content ratio of the cubic boron nitride relative to the cubic boron nitride sintered body is 20 volume % or more,

[0175] The TiAlN layer is determined by electron backscatter diffraction image analysis using a field emission scanning microscope on a cross section of the TiAlN layer cut along a plane including the normal line of the flank surface. x Al 1-x When the crystal orientation of each grain of N is determined and a color diagram is drawn based on the crystal orientation, in the color diagram,

[0176] In the TiAlN layer of the back face, the normal direction of the (111) plane is within 25° relative to the normal direction of the back face. x Al 1-xThe area ratio of N grains is 45% or more and less than 75%,

[0177] The residual stress of the TiAlN layer is greater than or equal to -2 GPa and less than or equal to -0.1 GPa.

[0178] (Note 2)

[0179] The surface-coated cutting tool according to Supplementary Note 1, wherein in the TiAlN layer of the flank surface, the normal direction of the (111) plane is within 25° relative to the normal direction of the flank surface. x Al 1-x The area ratio of N crystal grains is 55% or more and less than 75%.

[0180] (Note 3)

[0181] The surface-coated cutting tool according to Supplementary Note 1 or Supplementary Note 2, wherein the thickness of the coating is 0.5 μm or more and less than 10 μm.

[0182] (Note 4)

[0183] The surface-coated cutting tool according to any one of Supplementary Notes 1 to 3, wherein the TiAlN layer further contains Ar, and a content ratio of the Ar in the TiAlN layer is 0.1 at % to 5 at %.

[0184] (Note 5)

[0185] The surface-coated cutting tool according to any one of Supplementary Notes 1 to 4, wherein, in a cross section when the TiAlN layer is cut along a plane including a normal line of the flank surface, the number of droplets n per 50 μm length of the TiAlN layer on the flank surface is D Is less than 2.

[0186] Example

[0187] Hereinafter, the present invention will be described in detail with reference to Examples, but the present invention is not limited to these Examples.

[0188] [Experiment 1]

[0189] 《Manufacturing of cutting tools》

[0190] <Step 1: Preparation of substrate>

[0191] First, TiN, Ti and Al as binders are mixed to obtain a raw powder of the binder. Next, the raw powder of the binder is mixed with cubic boron nitride powder (cBN powder) to obtain a mixed powder. The obtained mixed powder is filled in a container. Under the conditions of pressure 5GPa and temperature 1400°C, the mixed powder filled in the container is sintered for 20 minutes to obtain a cubic boron nitride sintered body. The obtained cubic boron nitride sintered body is processed into the shape of ISO standard CNGA120408 to obtain a substrate of the cubic boron nitride sintered body.

[0192] <Production of film>

[0193] (Second step: preparation of TiAlN layer)

[0194] The TiAlN layer as the MAlN layer is formed by the HiPIMS method on the substrate of the cubic boron nitride sintered body obtained in step 1. That is, a plurality of targets are arranged in a film forming apparatus, and the substrate is mounted on a rotating substrate auxiliary fixture set at the center of these targets, and the film is formed according to the following steps.

[0195] First, the interior of the film-making device was decompressed to 20 mPa and then heated to about 550° C. Then, Ar gas was introduced. Then, a pulsed DC voltage of 800 V (frequency 50 kHz, pulse width 10 μs) was applied to the substrate in an atmosphere of 1000 mPa to generate Ar plasma, thereby etching the surface of the substrate (30 minutes).

[0196] Next, Ar gas and N2 gas are added to the interior of the film-making device so that the total pressure is adjusted to 300mPa (partial pressure: Ar is 200mPa, N2 is 100mPa). Then, a bias voltage of -80V is applied to the above-mentioned substrate, and a sputtering power (average power 10kW, frequency 2000Hz, pulse width 100μs) is applied to the cathode (TiAl sintered alloy as the target metal) to form a TiAlN layer by sputtering the target metal. In addition, the atomic ratio of Ti and the atomic ratio of Al in the TiAlN layer are adjusted by changing the respective ratios of Ti and Al in the target metal. The thickness of the TiAlN layer is adjusted by the film forming time. As described above, cutting tools with sample numbers 1 to 20 were produced.

[0197] For sample No. 14, a TiAlN layer was formed on the substrate using a conventional arc cathode ion plating method instead of the HiPIMS method.

[0198] (Production of base layer and surface layer)

[0199] For Sample Nos. 1 to 6 and 15 to 20, an underlayer was formed between the substrate of the cubic boron nitride sintered body and the TiAlN layer by HiPIMS. The composition and thickness of the underlayer are shown in Table 1.

[0200] In addition, for sample numbers 12 to 14, a surface layer was formed on the TiAlN layer using a cold cathode arc method. The composition and thickness of the surface layer are shown in Table 1. In Table 1 and Table 2 described later, items recorded in multiple samples are combined to indicate that they are the same in the multiple samples. For example, for the composition of the base layer in Table 1, sample numbers 1 to 6 are all represented as Al 0.7 Cr 0.3 N.

[0201] 《Evaluation of cutting tool characteristics》

[0202] Using the cutting tools of sample numbers 1 to 20 produced as described above, various characteristics of the cutting tools were evaluated as follows.

[0203] <Average particle size of cubic boron nitride>

[0204] The average particle size R of the cubic boron nitride in the cubic boron nitride sintered body was determined by the above-mentioned cutting method using a scanning electron microscope (SEM).

[0205] <Content ratio of cubic boron nitride>

[0206] The content ratio of cubic boron nitride in the cubic boron nitride sintered body was determined by the above method. That is, a cross-section sample of the cubic boron nitride sintered body was photographed using a SEM and the photographed image was analyzed to determine the content ratio. The results are shown in Table 1.

[0207] <Measurement of Thickness of Each Layer Constituting the Film>

[0208] The thickness of each layer constituting the coating (i.e., the thickness of the base layer, the TiAlN layer, and the surface layer) was determined by the following method: using SEM (manufactured by JEOL Ltd., trade name: JEM-2100F) to measure any 10 points in the cross-section sample parallel to the normal direction of the surface of the substrate, and to find the average value of the thickness of the 10 points measured. The observation magnification at this time was 10,000 times. The results are shown in Table 1.

[0209] <Ti x Al 1-x Determination of atomic ratio x of Ti in N>

[0210] Ti x Al 1-xThe atomic ratio x of Ti in N is obtained by the above method. That is, the value of x is obtained by measuring any 10 points in the TiAlN layer of the cross-section sample using a SEM-EDX device, and the average value of the values ​​of the 10 points is used as the TiAlN atomic ratio. x Al 1-x x in N. The results are shown in Table 1.

[0211] <Determination of Composition of Base Layer and Surface Layer>

[0212] The compositions of the base layer and the surface layer were determined by analyzing the entire layer to be analyzed in the cross-section sample using a SEM-EDX device.

[0213] <Measurement of Crystal Orientation in TiAlN Layer on Flank Face>

[0214] First, as described above, the cutting tool is cut to obtain a cross section perpendicular to the surface (or interface) of the TiAlN layer in the coating. Then, the cut surface is ground using water-resistant abrasive paper (manufactured by NCA Corporation, trade name: WATERPROOF PAPER, #400, #800, #1500), thereby producing a machined surface of the TiAlN layer. Next, the machined surface is further smoothed by ion milling using Ar ions. The conditions for the ion milling process are as follows.

[0215] Accelerating voltage: 6kV

[0216] Irradiation angle: 0° from the normal direction of the TiAlN layer (i.e., the straight line direction parallel to the thickness direction of the TiAlN layer on the cut surface)

[0217] Time: 8 hours

[0218] The above-mentioned processed surface was observed at a magnification of 5000 times using a FE-SEM equipped with EBSD (manufactured by Hitachi High-Tech Nolods, trade name: "SU6600"), thereby drawing the above-mentioned color map related to the observation area of ​​6μm (thickness direction of the TiAlN layer) × 50μm (direction parallel to the interface of the TiAlN layer) in the processed surface. And the number of drawn color maps (the number of measurement fields) is set to 3. Specifically, the crystal orientation of each grain contained in the cross section of the TiAlN layer is first determined. Then, based on the obtained crystal orientation of each grain, the crystal orientation of each grain in the normal direction of the surface of the TiAlN layer is determined. Then, based on the determined crystal orientation, a color map (for example Figure 6)。The proportion of the area occupied by (111)-oriented grains in the TiAlN layer on the flank face was determined for each color image using commercially available software (product name: “Orientation Imaging Microscopy Ver 6.2”, manufactured by EDAX). The results are shown in Table 2. In addition, based on the results of the above color images, a graph showing the distribution of the grain orientation in the TiAlN layer was drawn ( Figure 8 and Fig. 9 ).

[0219] <Measurement of Residual Stress in TiAlN Layer>

[0220] The residual stress in the TiAlN layer was determined by the above method. That is, the TiAlN layer was analyzed at any three points in the TiAlN layer by the 2θ-sin 2 ψ method (tilt method), and the average value of the residual stresses obtained at these three points was taken as the above residual stress of the TiAlN layer. The results are shown in Table 2.

[0221] <Measurement of Ar Content Ratio in TiAlN Layer>

[0222] The Ar content ratio in the TiAlN layer was determined by the above method. That is, the Ar content ratio was measured at any ten points in the TiAlN layer of the above cross-sectional sample using a SEM-EDX device, and the average value of the ten values obtained was taken as the Ar content ratio. The results are shown in Table 1.

[0223] <Measurement of Number of Droplets in TiAlN Layer on Flank Face>

[0224] The number of droplets per 50-μm length in the TiAlN layer was determined by the above method. That is, the above cross-sectional sample was observed at a magnification of 5000 times using a SEM to obtain a SEM image. At this time, a SEM image was acquired in such a way that the above TiAlN layer was continuously included in a 50-μm length range. By visually confirming the obtained SEM image, the number of droplets in a continuous 50-μm length range was counted. The results are shown in Table 2.

[0225] [Table 1]

[0226]

[0227] [Table 2]

[0228]

[0229] * refers to the number per 50-μm length in the TiAlN layer;

[0230] ** indicates the ratio of (100) oriented grains

[0231] 《Cutting Test》

[0232] (Cutting test 1: peripheral turning)

[0233] According to the following cutting conditions, the cutting tools of the samples (sample numbers 1 to 6 and sample numbers 15 to 20) prepared above were used to measure the cutting time (minutes) when the wear of the back face reached 0.2 mm or when the cutting edge portion broke. The results are shown in Table 2. The samples with long cutting time were evaluated as cutting tools with excellent wear resistance and chipping resistance. In this cutting test, sample numbers 2 to 5 and 16 to 19 correspond to embodiments. Sample numbers 1, 6, 15 and 20 correspond to comparative examples.

[0234] Cutting test 1 conditions

[0235] Cutting tool shape: CNGA120408

[0236] Cutting material: SCM415H (HRC60), (cylindrical parts with a diameter of 100 mm and a length of 250 mm)

[0237] Cutting speed: 180m / min

[0238] Feed rate: 0.2mm / revolution

[0239] Cutting amount: 0.2mm

[0240] Cutting oil: dry

[0241] From the results in Table 2, it can be seen that the cutting tools of sample numbers 2 to 5 achieved good results with a cutting time of 21 minutes or more. On the other hand, the cutting time of the cutting tools of sample numbers 1 and 6 was 9 minutes or less. From the above results, it can be seen that the cutting tools of the examples are excellent in wear resistance and chipping resistance.

[0242] From the results in Table 2, it can be seen that the cutting tools of sample numbers 16 to 19 achieved good results with a cutting time of more than 10 minutes. On the other hand, the cutting time of the cutting tools of sample numbers 15 and 20 was less than 5 minutes. From the above results, it can be seen that the cutting tools of the examples are excellent in wear resistance and chipping resistance.

[0243] (Cutting test 2: peripheral turning)

[0244] According to the following cutting conditions, the cutting tools of the samples (sample numbers 7 to 11) prepared above were used to count the number of cut materials processed until the wear amount of the back cutting surface reached 0.2 mm or the cutting edge portion was chipped (hereinafter sometimes referred to as "the number of cut materials"). The results are shown in Table 2. The samples with a large number of cut materials were evaluated as cutting tools with excellent chipping resistance. In this cutting test, sample numbers 8 to 10 correspond to embodiments. Sample numbers 7 and 11 correspond to comparative examples.

[0245] Cutting test 2 conditions

[0246] Cutting tool shape: CNGA120408

[0247] Cutting material: SCM415H (HRC60), (a component with four grooves (5mm width, 5mm depth) at 90-degree intervals on the outer circumference of a cylinder with a diameter of 50mm and a length of 100mm. 40mm of the outer circumference is processed from one end along the length direction)

[0248] Cutting speed: 120m / min

[0249] Feed rate: 0.1mm / turn

[0250] Cutting amount: 0.2mm

[0251] Cutting oil: dry

[0252] From the results in Table 2, it can be seen that the cutting tools of sample numbers 8 to 10 obtained good results when the number of cut materials was 4 or more. On the other hand, the number of cut materials of the cutting tools of sample numbers 7 and 11 was 1 or less. From the above results, it can be seen that the cutting tools of the examples are excellent in chipping resistance.

[0253] (Cutting test 3: peripheral turning)

[0254] According to the following cutting conditions, the cutting tools of the samples (sample numbers 12 to 14) prepared above were used to measure the cutting time (minutes) when the wear of the back face reached 0.2 mm. The results are shown in Table 2. The samples with long cutting time were evaluated as cutting tools with excellent wear resistance. In this cutting test, sample number 12 is equivalent to the embodiment. Sample numbers 13 and 14 are equivalent to comparative examples.

[0255] Cutting test 3 conditions

[0256] Cutting tool shape: CNGA120408

[0257] Cutting material: SUJ2 (HRC62), (cylindrical parts with a diameter of 140 mm and a length of 300 mm)

[0258] Cutting speed: 120m / min

[0259] Feed rate: 0.1mm / turn

[0260] Cutting amount: 0.1mm

[0261] Cutting oil: Wet type

[0262] As can be seen from the results in Table 2, the cutting tool of sample number 12 achieved a good result of 14 minutes of cutting time. On the other hand, the cutting time of the cutting tools of sample numbers 13 and 14 was 6 minutes or less. From the above results, it can be seen that the cutting tools of the examples are excellent in wear resistance.

[0263] [Experiment 2]

[0264] 《Manufacturing of cutting tools》

[0265] <Step 1: Preparation of substrate>

[0266] By the same method as in Experiment 1, a substrate of a cubic boron nitride sintered body having a shape in accordance with ISO standard CNGA 120408 was obtained.

[0267] <Production of film>

[0268] (Second step: preparation of MAlN layer)

[0269] The MAlN layer was formed on the substrate by the same method as in Experiment 1 except that the target was changed so that the MAlN layer had the composition shown in Table 3. As described above, cutting tools with sample numbers 21 to 38 were produced. It should be noted that the cutting tools with sample numbers 21 to 38 were all configured such that the coating did not include a base layer and a surface layer.

[0270] 《Evaluation of cutting tool characteristics》

[0271] The cutting tools of sample numbers 21 to 38 prepared above were used in the same manner as in Experiment 1 to evaluate the various properties of the cutting tools. The results are shown in Tables 3 and 4.

[0272] 《Cutting Test》

[0273] (Cutting test 4: peripheral turning)

[0274] According to the following cutting conditions, using the cutting tools of the samples (sample numbers 21 to 29) prepared above, the cutting time (minutes) when the wear of the back face reaches 0.2 mm or when the cutting edge portion breaks is measured. The wear of the above-mentioned back face is measured every 5 minutes from the start of cutting. The results are shown in Table 4. The samples with long cutting time are evaluated as cutting tools with excellent wear resistance and chipping resistance. In this cutting test, sample numbers 21 to 28 are equivalent to embodiments. Sample number 29 is equivalent to the comparative example.

[0275] Cutting test 4 conditions

[0276] Cutting tool shape: CNGA120408

[0277] Cutting material: SCM415H (HRC60), (cylindrical parts with a diameter of 100 mm and a length of 250 mm)

[0278] Cutting speed: 220m / min

[0279] Feed rate: 0.2mm / revolution

[0280] Cutting amount: 0.2mm

[0281] Cutting oil: dry

[0282] (Cutting test 5: peripheral turning)

[0283] According to the following cutting conditions, the cutting tool of the samples (sample numbers 30 to 33) prepared above was used to count the number of cut materials processed until the wear amount of the back cutting edge reached 0.2 mm or the cutting edge portion was chipped (hereinafter sometimes referred to as "the number of cut materials"). The results are shown in Table 4. Samples with a large number of cut materials (for example, more than 5) were evaluated as cutting tools with excellent wear resistance and chipping resistance. In this cutting test, sample numbers 30 to 33 correspond to the embodiments.

[0284] Cutting test 5 conditions

[0285] Cutting tool shape: CNGA120408

[0286] Work material: SCM415H (HRC60), (a component with a groove (2mm width, 5mm depth) on the outer circumference of a cylinder with a diameter of 50mm and a length of 100mm. The outer circumference is machined to 40mm along the length direction from one end)

[0287] Cutting speed: 100m / min

[0288] Feed rate: 0.1mm / turn

[0289] Cutting amount: 0.1mm

[0290] Cutting oil: dry

[0291] (Cutting test 6: peripheral turning)

[0292] According to the following cutting conditions, the cutting tools of the samples (sample numbers 34 to 38) prepared above were used to measure the cutting time (minutes) when the wear of the back face reached 0.2 mm. The wear of the back face was measured every 5 minutes from the start of cutting. The results are shown in Table 4. The samples with long cutting time were evaluated as cutting tools with excellent wear resistance and chipping resistance. In this cutting test, sample numbers 34 and 35 are equivalent to embodiments. Sample numbers 36 to 38 are equivalent to comparative examples.

[0293] Cutting Test 6 Conditions

[0294] Cutting tool shape: CNGA120408

[0295] Cutting material: SUJ2 (HRC62), (cylindrical parts with a diameter of 140 mm and a length of 300 mm)

[0296] Cutting speed: 150m / min

[0297] Feed rate: 0.2mm / revolution

[0298] Cutting amount: 0.1mm

[0299] Cutting oil: Wet type

[0300] [Table 3]

[0301]

[0302] * Samples 21 to 38 did not form a base layer or a surface layer.

[0303] [Table 4]

[0304]

[0305] * Refers to the number per 50 μm length of the MAlN layer

[0306] As can be seen from the results in Table 4, the cutting tools of Examples have excellent wear resistance and excellent chipping resistance.

[0307] As mentioned above, although embodiment and example of the present invention have been described, it is initially contemplated that the configurations of the above-mentioned embodiments and examples can be appropriately combined.

[0308] The embodiments and examples of the present disclosure should be considered to be illustrative in all aspects and not restrictive. The scope of the present invention is not limited to the above embodiments and examples, but is represented by the claims, and is intended to include all changes within the meaning and scope equivalent to the claims.

[0309] Explanation of symbols

[0310] 1a rake face, 1b flank face, 1c cutting edge face, 10 cutting tool, 11 substrate, 12 MAlN layer, 12a (111) plane oriented grains, 13 base layer, 14 surface layer, 20 coating.

Claims

1. A cutting tool comprising a rake face and a flank face, The cutting tool is composed of a substrate composed of a cubic boron nitride sintered body and a coating provided on the substrate. The cubic boron nitride sintered body contains cubic boron nitride. The coating includes a MAlN layer, The M in the MAlN layer represents a metal element including titanium, chromium, or both. The MAlN layer contains cubic M x Al 1-x N grains, The M x Al 1-x The atomic ratio x of the metal element M in N is 0.3 or more and 0.7 or less, The content ratio of the cubic boron nitride relative to the cubic boron nitride sintered body is 20 volume % or more, The MAlN layer is determined by electron backscatter diffraction image analysis using a field emission scanning microscope on a cross section of the MAlN layer cut along a plane including the normal line of the flank surface. x Al 1-x When the crystal orientation of each grain of N is determined and a color diagram is drawn based on the crystal orientation, in the color diagram, In the MAlN layer of the flank surface, the normal direction of the (111) plane is within 25° relative to the normal direction of the flank surface. x Al 1-x The area ratio of N grains is 45% or more and less than 75%, The residual stress of the MAlN layer is not less than -2 GPa and not more than 0.1 GPa. In a cross section when the MAlN layer is cut along a plane including a normal line of the flank surface, the number n of droplets per 50 μm length of the MAlN layer on the flank surface is D is less than 2, The droplet is a metal particle present in the MAlN layer, and the droplet has a length L of a long side of an imaginary rectangle circumscribing the metal particle in the cross section. a μm and the length of the short side L b μm Particles with a size that satisfies the following conditions: 1≤L a / L b <1.3、and 0.1<L a , in, The long side or the short side is parallel to the main surface of the substrate.

2. The cutting tool according to claim 1, in, The metal element M further includes at least one element selected from the group consisting of vanadium, zirconium, niobium, molybdenum, hafnium, tantalum, and tungsten.

3. A cutting tool comprising a rake face and a flank face, The cutting tool is composed of a substrate composed of a cubic boron nitride sintered body and a coating provided on the substrate. The cubic boron nitride sintered body contains cubic boron nitride. The coating includes a MAlN layer, The M in the MAlN layer represents an element including titanium, chromium, or both, and the element M further includes at least one element selected from the group consisting of boron and silicon. The MAlN layer contains cubic M x Al 1-x N grains, The M x Al 1-x The atomic ratio x of the element M in N is 0.3 or more and 0.7 or less, The content ratio of the cubic boron nitride relative to the cubic boron nitride sintered body is 20 volume % or more, The MAlN layer is determined by electron backscatter diffraction image analysis using a field emission scanning microscope on a cross section of the MAlN layer cut along a plane including the normal line of the flank surface. x Al 1-x When the crystal orientation of each grain of N is determined and a color diagram is drawn based on the crystal orientation, in the color diagram, In the MAlN layer of the flank surface, the normal direction of the (111) plane is within 25° relative to the normal direction of the flank surface. x Al 1-x The area ratio of N grains is 45% or more and less than 75%, The residual stress of the MAlN layer is not less than -2 GPa and not more than 0.1 GPa. In a cross section when the MAlN layer is cut along a plane including a normal line of the flank surface, the number n of droplets per 50 μm length of the MAlN layer on the flank surface is D is less than 2, The droplet is a metal particle present in the MAlN layer, and the droplet has a length L of a long side of an imaginary rectangle circumscribing the metal particle in the cross section. a μm and the length of the short side L b μm Particles with a size that satisfies the following conditions: 1≤L a / L b <1.3、and 0.1<L a , in, The long side or the short side is parallel to the main surface of the substrate.

4. The cutting tool according to any one of claims 1 to 3, in, In the MAlN layer of the flank surface, the normal direction of the (111) plane is within 25° relative to the normal direction of the flank surface. x Al 1-x The area ratio of N crystal grains is 55% or more and less than 75%.

5. The cutting tool according to any one of claims 1 to 3, in, The coating has a thickness of 0.5 μm or more and less than 10 μm.

6. The cutting tool according to any one of claims 1 to 3, in, The MAlN layer further contains Ar, and the content ratio of the Ar in the MAlN layer is 0.1 at % to 5 at %.

Citation Information

Patent Citations

  • Combined material having high hardness for tool

    JP1996119774A

  • Printing system and control method of printing system

    JP2019144611A

  • Wear-resistant film, and surface-coated cutting tool using the same

    JP2005344148A

  • Nitride-containing target material

    JP2008106287A

  • Film deposition method and film deposition apparatus

    JP2010084153A